A review of fluid-structure interaction simulation for patients with sleep related breathing disorders with obstructive sleep. (October 2019) - Faizal, W.M.; Ghazali, N.N.N.; Badruddin, Irfan Anjum; Zainon, M.Z.; Yazid, Aznijar Ahmad; Ali, Mohamad Azlin Bin; Khor, C.Y.; Ibrahim, Norliza Binti; Razi, Roziana M.
Highlights: This paper provides a comprehensive review of fluid-structure interaction as used to evaluate breathing disorders in patients with obstructive sleep apnea. The present article serves as a guideline for researchers having the ambition to work in the area of obstructive sleep apnea. The current article fills the gap of non-availability of a review in the field of obstructive sleep apnea for quite some time. Abstract: Obstructive sleep apnea is one of the most common breathing disorders. Undiagnosed sleep apnea is a hidden health crisis to the patient and it could raise the risk of heart diseases, high blood pressure, depression and diabetes. The throat muscle (i.e., tongue and soft palate) relax narrows the airway and causes the blockage of the airway in breathing. To understand this phenomenon computational fluid dynamics method has emerged as a handy tool to conduct the modeling and analysis of airflow characteristics. The comprehensive fluid-structure interaction method provides the realistic visualization of the airflow and interaction with the throat muscle. Thus, this paper reviews the scientific work related to the fluid-structure interaction (FSI) for the evaluation of obstructive sleep apnea, using computational techniques. In total 102 articles were analyzed, each article was evaluated based on the elements related with fluid-structure interaction of sleep apnea via computational techniques. In this review, the significance of FSI for the evaluation of obstructive sleep apnea has been critically examined. Then the flow properties, boundary conditions and validation of the model are given due consideration to present a broad perspective of CFD being applied to study sleep apnea. Finally, the challenges of FSI simulation methods are also highlighted in this article.